PSYCHOLOGICAL STRESS FACTORS AFFECTING THE STABILITY OF MANAGERIAL PERSONNEL IN ORGANIZATIONS AND THEIR IMPACT ON MANAGEMENT EFFECTIVENESS - Qoshsheaev Umid Tohirovich (International Journal of Business, Law and Political Science, 2026)
Objective: This article analyzes psychological stress factors affecting the stability of managerial personnel in organizations and their impact on management effectiveness. Method: It examines the main causes of stress among managers, including high workload, increased responsibility, and the socio-psychological climate within organizations. The study focuses on the influence of stress on managers’ emotional states, decision-making processes, and motivational stability. Results: It also explores the psychological reasons behind managerial turnover and its negative consequences for organizational efficiency. Novelty: Furthermore, the article provides recommendations for stress management and improving the psychological resilience of managers.